Challenges for Indonesia in Case of Liberalization of Trade in Services in The ASEAN Economic Community - Magdariza, Magdariza (UI Scholars Hub, 2017)
Cooperation among ASEAN countries formed since 1967 through Bangkok Declaration. In development, ASEAN agreed to establish ASEAN Community in 2020. This relationship was upgraded within the ASEAN Summit in Singapore in 2007 which agreed on the ASEAN Charter to strengthen the position and legal status of ASEAN in realizing the cooperation among ASEAN countries, and as a guide in ASEAN Community formation, the Blueprint is prepared. One of the pillars of ASEAN Community is the establishment of ASEAN Economic Community, which talk about liberalization of trade in services. The implementation of the trade liberalization in ASEAN will increasing and provide convenience and also increased intra-ASEAN market access as well increasing transparency and speeding up the adjustment of regulations and standardization of domestic. Indonesia already ratified ASEAN Charter with Law No. 8 of 2008. Therefore, Indonesia is obliged to implement the provisions of ASEAN Charter. Treaty on liberalization of trade in sevices has been initiated in ASEAN Framework Agreement (AFAS) in 1995 and Indonesia also ratified by Presidential Decree No. 88 in 1995. Law No. 7/2014 on Trade, also regulates the trade in services as Indonesia’s commitment within the ASEAN Economic Community. The liberalization of trade in services within ASEAN framework is a challenge for Indonesia to prepare human resources or skilled menpower with competence to compete with menpower from other ASEAN countries. This situation can also be used as an opportunity for Indonesia to prepare and compete with other ASEAN members but on the other hand they can be vast potential market for ASEAN countries.